Connecting priority algorithm for node deployment in directional sensor networks. (2017) - Tan, Li; Chen, Yucheng; Yang, Minghua; Hu, Jipeng; Lian, Jingjing
According to the existing directional sensor networks, the centroid point of node model mostly rotate around the sector vertex. As in this model, the node rotation area is a full circle, therefore multiply the network energy consumption and deployment time. This paper is based on the new directional model in which the sector nodes rotate around the centroid, then we present a potential field based connecting priority algorithm for node deployment, and finally make simulation for this algorithm to explore the parameters which will affect the coverage ratio. The simulation results show the effectiveness of the model and algorithm.